Comparison Of The Effectiveness Of Irrigation and Manual Extraction Techniques On The Comfort Level Of Serumen-Impacted Patients Using The Kolcaba Comfort Theory Approach - Yobel, Sosilo (STIKES Adi Husada, 2023)
A buildup of cerumen, or earwax, in the ear canal is one of the most common problems experienced by patients and, if ignored, can cause hearing loss, irritation, and discomfort. Comfort is an integral part of nursing work as a client's basic needs which is the goal of nursing work. The nursing approach to providing comfort to patients is based on Kolcaba's comfort theory. This theory includes comfort in four contexts of comfort, namely: physical, psychospiritual, sociocultural, and environmental. The purpose of this study was to compare irrigation techniques' effectiveness with manual extraction on the comfort level of cerumen-impacted patients using the Kolcaba comfort theory approach. This research is pre-experimental research with a